2020
DOI: 10.4158/accr-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Abscess After Injection of Heroin into the Neck Complicated by Thyroid Storm

Abstract: Objective: Our objective is to present a case of thyroid abscess complicated by thyroid storm secondary to intravenous drug use. Cases of thyroid abscess causing thyrotoxicosis are rare. This is the first report of thyroid abscess from intrathyroidal injection of illicit drugs resulting in thyroid storm. Methods: We used biochemical evaluation, computed tomography (CT), and ultrasound to assess the thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Similarly, Shrum et al [140] presented a suicide attempt by hanging that caused TS and cardiac arrest. Mathai et al [117] reported a case of TS that was precipitated by injecting heroin into the neck. Kaplakam et al described bedside tracheostomy as a possible trigger for TS [123].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shrum et al [140] presented a suicide attempt by hanging that caused TS and cardiac arrest. Mathai et al [117] reported a case of TS that was precipitated by injecting heroin into the neck. Kaplakam et al described bedside tracheostomy as a possible trigger for TS [123].…”
Section: Discussionmentioning
confidence: 99%